Evaluation of Paulownia elongata wood polyethylene composites. (September 2015) - Tisserat, Brent; Reifschneider, Louis; Joshee, Nirmal; Finkenstadt, Victoria L
Paulownia wood flour (PWF), a by-product of milling lumber, was employed as a biofiller and blended with high-density polyethylene (HDPE) via extrusion. Paulownia wood (PW) shavings were milled through a 1-mm screen and then separated via shaking into various particle fractions (600–≤74 µm) using sieves (#30–>#200 US Standards). The influence of a commercial coupling agent, maleated polyethylene (MAPE), used at various concentrations (0, 1, 3, 5, or 10% w/w) with HDPE and wood particles obtained from a #50-mesh sieve, is examined. Incorporation of high concentrations of MAPE (approximately 5%) in HDPE-PWF blends improved tensile strength compared to lower MAPE concentrations (≤3%). Particle size of wood significantly influenced the mechanical properties of the biocomposite. HDPE-MAPE blends containing smaller wood particles (<180 µm) had higher tensile strength than neat HDPE or blends containing larger particles (>300 µm). Young's modulus for all HDPE-PWF-MAPE blends was 14–27% higher than that of neat HDPE. Generally, incubation of tensile bars of various HDPE-PWF blends in 95% humidity for 28 days reduced the mechanical properties approximately by 5%. Differential scanning calorimetry analysis showed a slight reduction in the percentage crystallinity among various HDPE-PW blends.